Post-qualitative Inquiry and CHAT's Formative Interventions: Epistemological Legitimacy Beyond Methodological Concerns - Andrea Mattia Marcelli; Daniele Morselli (Pensa MultiMedia, 2022)
Cultural-historical activity theory (CHAT) appears to match the tenets of post-qualitative inquiry. However, post-qualitative inquiry is credited with being averse to method and to adopt post-modernist stances that are not consistent with CHAT's structured reading of social reality. Notwithstanding this, it is possible to propose an interpretation of post-qualitative inquiry that overcomes such conceptual challenges. This article tackles the issue both theoretically and with reference to the way current CHAT research is undertaken. First, we propose post-qualitative research should be understood as compliant with post-Gettier epistemological standpoints. Second, we show that CHAT-inspired formative interventions are both educational in nature and, given their approach to learning processes, display the core features of post-qualitative research. Given CHAT's distinction between immanent aspects of social reality and methods tailored to tackle local issues, post-qualitative inquiry is justified in retaining its flexible-almost anarchic-methodology while, at the same time, enjoying epistemological soundness.